On Making Them All One: Unity, Transcendence and the Anglican Church - Baker, Anthony D. (Journal of Anglican studies, 2007)
The question of unity looms large in current vocabulary of the Anglican Communion. This article suggests, first of all, that the term is a rich theological one that ought to come under rigorous theological scrutiny and, secondly, that such scrutiny could in fact alter the way Anglicans understand themselves as an ecclesial body. While the works of Rowan Williams and Ephraim Radner have issued important and necessary calls for a return to ecclesiology, both, it is here suggested, do not illuminate fully the implications of the New Testament call to ‘be one’. Making substantial reference to Hooker's theology of the church, which is properly seen as an extension of his Christology, it is here suggested that unity is both a gift that transcends the church in its descent in the Spirit, and a craft that takes shape as the church struggles to make and remake itself in the image of Christ, whose prayer that his followers would all be one as ‘you and I’ is one that has consistently supplied the framework for the tradition of Christian ecclesiology.